Modelling semantic kernel of web resource - Orekhov, Sergey Valerievich; Malyhon, Hennadiy Vasilievich (Національний технічний університет "Харківський політехнічний інститут", 2021)
The article presents an attempt to describe mathematically the effect of the semantic kernel of a web resource on the Internet. In accordance with the theory of marketing, the product that we want to sell on the network is characterized by the following basic properties: price, time and place. In other words, a potential buyer wants to receive a given product in the right place at a given time. To satisfy this need, it is necessary to use the classic component of marketing, product promotion. However, this component is now becoming a fully virtual instrument. This tool functions in a hypertext, video and image environment. Therefore, the user analyzes the meaning of these elements in order to get the desired product. The results of web projects carried out in this area indicate the emergence of a new phenomenon, which reflects the main meaning of virtual promotion – this is the semantic core. The core is a short annotation of the main properties of the product, its location and time of appearance. Therefore, the purpose of this article is both a presentation of a new object of research and a mathematical description. It is assumed that the semantic core is formed on the basis of natural language terms. In other words, the semantic core is a set of keywords that are grouped by meaning. We propose to use data mining approaches for clustering to group terms. The classic clustering method at the moment is k-means. The article presents a model of the semantic core based on this method. This method and its distance function are considered as the second stage of web content processing. At the first stage, web content is converted into a semantic web. However, the k-means technique has significant drawbacks when modeling the semantic core. Therefore, in the development of this idea, the work shows an alternative way to modeling the kernel. As an alternative approach, the construction of clusters based on the concept of maximum flow is considered. This approach has the significant advantage that the type of links in the semantic network overlaps with the type of distance function in this method. As a result, on a real web project, the effect of the connection between the semantic core model and the level of new users of the web resource was demonstrated over the past five years.

У статті представлена спроба описати математично ефект семантичного ядра веб ресурсу в середовищі Інтернет. Відповідно до теорії маркетингу продукт, який ми бажаємо продати в мережі, характеризуються такими основними властивостями: ціна, час і місце. Іншими словами потенційний покупець бажає отримати заданий товар в потрібному місці в заданий час. Щоб задовольнити цю потребу, треба використовувати класичну компоненту маркетингу просування товару. Однак зараз ця компонента стає повністю віртуальним інструментом. Цей інструмент функціонує в середовищі гіпертекстів, відео та зображень. Тому користувач аналізує зміст даних елементів, щоб отримати бажаний товар. Результати виконаних в цій області веб проектів свідчать про появу нового явища, яке відображає основний зміст віртуального просування – це семантичне ядро. Ядро являє собою коротку анотацію основних властивостей товару, його місце розташування і час появи. Тому метою даної статті є як презентація нового об'єкта дослідження, так і математичний опис. Передбачається, що семантичне ядро формується на основі термінів природної мови. Іншими словами семантичне ядро – це безліч ключових слів, які згруповані за змістом. Ми пропонуємо використовувати для угрупування термінів підходи технології Data mining по кластеризації. Класичним методом кластеризації на даний момент є k-середніх. У статті представлена модель семантичного ядра на основі даного методу. Цей метод і його функції дистанції розглядаються як другий етап обробки веб контенту. На першому етапі веб контент конвертується в семантичну мережу. Однак методика k-середніх має суттєві недоліки при моделюванні семантичного ядра. Тому в розвитку даної ідеї в роботі показаний альтернативний шлях до моделювання ядра. В якості альтернативного підходу розглядається побудови кластерів на основі концепції максимального потоку. Цей підхід має істотну перевагу, яке полягає в тому, що тип зв'язків в семантичної мережі перегукується з типом функції дистанції в даному методі. В результаті на реальному веб проект продемонстрований ефект зв'язку між моделлю семантичного ядра і рівнем нових користувачів веб ресурсу протягом останніх п'яти років.
Моделювання семантичного ядра веб ресурсу
Keywords: keyword; k-means; max flow; ключове слово; метод k-середніх; максимальний потік